Peran Bawaslu dan Mahasiswa FISIP UNTAN Pontianak Dalam Membangun Partisipatif Pemilih Pemula pada Pilkada 2024 - Auwaliyah, Nur Hadis; Ridwan, Ridwan; Indri Listiani, Endang; Ningsih, Tirta Rahayu; Donatus Aldo, Fransiskus; Ayudia, Leony; Puspita Putri , Kristin Apriliani; Jessica, Kristina; Haikal Adi Noor, Muhammad; Fatma Yanti Ilham, Nur; Erlangga, Rendy; Suryadi, Rian; Ema Rahmaniah, Syarifah (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
This study aims to enhance understanding and build participation among first-time voters in the 2024 Regional Election through socialization activities conducted by students of the Community Service Program (MBKM) of the Faculty of Social and Political Sciences (FISIP) of UNTAN in collaboration with the General Election Supervisory Agency (Bawaslu) of Pontianak City. The research employs a qualitative method utilizing secondary data. Data collection techniques include literature review and observation. In this activity, students, together with Bawaslu, conducted direct socialization at SMA SANTUN UNTAN and held a meeting at Harris Hotel, Pontianak City, to provide insights into the election process, the importance of exercising voting rights, and the role of election supervision. The results indicate high enthusiasm from students during the question-and-answer session, reflecting an increased understanding of the importance of participation and oversight in the electoral process. The activities also created an interactive and enjoyable learning environment through rewards for active participants, thus encouraging student participation in the elections. It is hoped that this socialization will foster a generation of informed, critical, and actively engaged first-time voters in Indonesia's democracy.